Effects of shading on photosynthetic characteristics and shade-tolerance evaluation of three Ranunculaceae plants - HAN Ruiting, ZHAO Dandan, WANG Weiyi, ZHANG Gexiang* (Guangxi Zhiwu)
In order to investigate the response mechanism of Ranunculus japonicus, Thalictrum fortunei and Delphinium anthriscifolium var. savatieri in different light environments, five shade treatment levels(0%, 30%, 50%, 70% and 90% shade degrees)were set in this study, the photosynthetic indexes of the three plants were determined, and the effects of different shade treatments on their photosynthetic characteristics and shade-tolerance evaluation were studied. The results were as follows: with the increase of shading degree,(1)The contents of chlorophyll a, chlorophyll b, chlorophyll(a+b)and carotenoid increased, while the content of chlorophyll a/b decreased.(2)The apparent quantum yield(AQY)of the three plants increased first and then decreased; the maximum net photosynthetic rate(Pmax)of Ranunculus japonicus and Delphinium anthriscifolium var. savatieri showed a trend of first rising and then decreasing, while the Pmax of Thalictrum fortunei showed a decreasing trend. The light saturation point(LSP), light compensation point(LCP)and dark respiration rate(Rd)of the three plants decreased gradually.(3)The original fluorescence(Fo)decreased first and then increased, while the maximum fluorescence(Fm), variable fluorescence(Fv), maximum photochemical efficiency of PS Ⅱ(Fv/Fm)and potential activity of PS Ⅱ(Fv/Fo)values increased first and then decreased; the quantum ratio of heat dissipation(φDo)and the energy dissipated per unit reaction center(DIo/RC)decreased first and then increased, while electron transport quantum yield(φEo), light energy absorbed per unit reaction center(ABS/RC), light energy captured per unit reaction center(TRo/RC), energy used to transfer electrons per unit reaction center(ETo/RC), photosynthetic performance index(PIabs)and comprehensive performance index(PItotal)increased first and then decreased.(4)Comprehensive analysis on 20 single indicators by using analysis methods such as principal component analysis and membership function method showed that the shade-tolerance of the three plants ranked as Thalictrum fortunei > Delphinium anthriscifolium var. savatieri > R. japonicus. In conclusion, the three species have different adaptability to light, which provides a reference for the application of Ranunculaceae plants in landscaping.